Five Neuropeptide Ligands Meet One Receptor: How Does This Tally? A Structure-Activity Relationship Study Using Adipokinetic Bioassays With the Sphingid Moth, Hippotion eson - Marco, Heather G.; Gäde, Gerd (Frontiers in Endocrinology, 2019)
Adipokinetic hormones (AKHs) play a major role in mobilizing stored energy metabolites during energetic demand in insects. We showed previously (1) the sphingid moth Hippotion eson synthesizes the highest number of AKHs ever recorded, viz. five, in its corpus cardiacum: two octa- (Hipes-AKH-I and II), two nona- (Hipes-AKH-III and Manse-AKH) and one decapeptide (Manse-AKH-II), which are all active in lipid mobilization (Gäde et al. 2013). (2) Lacol-AKH from a noctuid moth showed maximal AKH activity in H. eson despite sequence differences and analogs based on Lacol-AKH with modifications at positions 2, 3, 8 or at the termini, as well as C-terminally shortened analogs had reduced or no activity (Marco and Gäde, 2015). Here we report on N-terminally shortened and modified analogs of the lead peptide, as well as single amino acid substitutions at positions 1, 4, 5, 6 and 7 by an alanine residue. Ala1 and Glu1 instead of pGlu are not tolerated well to bind to the H. eson AKH receptor, whereas Gln1 has high activity, suggesting it is endogenously cyclized. Replacing residue 5 or 7 with Ala did not alter activity much, in contrast with changes at position 4 or 6. Similarly, eliminating pGlu1, Leu2, or Thr3 from Lacol-AKH severely interfered with biological activity. This indicates that there is no core peptide sequence that can elicit the adipokinetic effect and that the overall conformation of the active peptide is required for a physiological response. AKHs achieve a biological action through binding to a receptor located on fat body cells. To date, one AKH receptor has been identified in any given insect species; we infer the same for H. eson. We aligned lepidopteran AKH receptor sequences and note that these are very similar. The results of our study is, therefore, also applicable to ligand-receptor interaction of other lepidopteran species. This information is important for the consideration of peptide mimetics to combat lepidopteran pest insects.